Предмет: Алгебра,
автор: rizhik22
-3x(2x-1) помогите решить
Ответы
Автор ответа:
0
-3х(2х-1)
-3х+2х-3х(-1)
2
Ответ: -6х +3х
-3х+2х-3х(-1)
2
Ответ: -6х +3х
mashkodenko1:
тут умножить надо было на скобочку,а ты сложил
Автор ответа:
0
-3х(2х-1)
-6х^2+3х
-6х^2=-3/:(-3)
2х^2=1/:2
х^2=0,5
х1=-0,5
х2=0,5
-6х^2+3х
-6х^2=-3/:(-3)
2х^2=1/:2
х^2=0,5
х1=-0,5
х2=0,5
Похожие вопросы
Предмет: Физика,
автор: kolesovaemilia1
Предмет: География,
автор: karinabilova76
Предмет: Физика,
автор: zskfkzszekiw6
Предмет: Математика,
автор: ник2854
Предмет: Математика,
автор: fashion007